Rates of hospitalization among patients with deep vein thrombosis before and after the introduction of rivaroxaban. Issue 2 (May 2015) - Merli, Geno J.; Hollander, Judd E.; Lefebvre, Patrick; Laliberté, François; Raut, Monika K.; Olson, William H.; Pollack, Charles V.
Abstract: Background . Compared to warfarin, the non-vitamin K antagonist oral anticoagulant rivaroxaban may have advantages in treating patients with venous thromboembolism, because injectable bridging therapy and routine laboratory monitoring are not required. The objective of this study was to compare the rate of hospitalization in patients treated with rivaroxaban after its introduction with what it would have been before the introduction of rivaroxaban. Methods . A retrospective claims analysis was conducted using the MarketScan Hospital Drug Database from January 2011 to December 2013. Adult patients with a primary diagnosis of deep vein thrombosis (DVT) treated with rivaroxaban or low-molecular-weight heparin (LMWH) bridged to warfarin during the first day of an evaluation at a hospital were identified. Based on propensity-score methods, historical LMWH/warfarin patients (i.e., patients who received LMWH/warfarin before the approval of rivaroxaban) were matched 4:1 to rivaroxaban patients, and the rates of hospitalization were compared. Results . All rivaroxaban-treated patients (n = 134) in the database were well matched with four historical LMWH/warfarin-treated patients (n = 536). Among the rivaroxaban cohort, 60% of the patients were admitted to the hospital, compared to 82% of the historical patients treated with LMWH/warfarin in the matched cohort. The difference was statistically significant and corresponded to a 27% reduction in hospital admissions (rate ratio [95% confidence interval]: 0.73 [0.62–0.84]). Hospital admission rates adjusted for time-trend analyses also led to similar results. Conclusion. The availability of rivaroxaban significantly reduced the hospitalization rate in patients with DVT treated with rivaroxaban compared to what it would have been if only LMWH/warfarin were available.